Securitization of tourism activities to defend national interest - Galih A Putra; Helda Risman (Universitas Pertahanan Republik Indonesia (UNHAN RI), 2022)
Indonesia's current dynamic of tourism activities brings about positive impacts such as increasing the GDP and making good diplomatic relations. On the other hand, it can also create security threats, including terrorism, crime, and a new variant of the COVID-19 virus appearance. These issues impacted many stakeholders from the states up to the society. This research aims at explaining the securitization of tourism activities interfered with the defense of Indonesia's national interests by conducting a descriptive analysis method based on data from books, previous research, and some regulations. It portrays many challenges faced by Indonesia and the opportunities they get to defend national interest from the securitization of tourism activities. It also shows that the government's strategy in measuring security threats needs to be done hand-in-hand with all stakeholders to increase the effectiveness.